Review of large-scale CLT compartment fire tests - Liu, Julie; Fischer, Erica C. (Construction & building materials, 2022)
•Previous research has focused on flashover fires in a limited range of compartment sizes.•Methods of predicting self-extinction at realistic scales have not yet been well-established.•Few tests have included structural loads on the roof of the fire compartment, and limited data is available on structural response.•Tests where timber surfaces have been left unprotected have typically exceeded the limits on unprotected timber surfaces set by the International Building Code. Cross-laminated timber (CLT) is a mass timber product that has attracted increasing interest in mid- and high-rise building construction. However, conventional compartment fire models were developed for non-combustible construction. As a result, numerous large-scale fire tests have been conducted in recent years to investigate the fire behavior of both fully and partially protected CLT compartments with the goal of quantifying the fire behavior of CLT structures and further developing codes and standards. Previous tests have consisted of a limited range of compartment sizes, and test protocols and data reporting have varied widely between test series. Test series have utilized different ventilation conditions, structure types, fuel types, and applied mechanical loads. Although gas temperatures and total heat release rates are frequently included in test results, other data such as incident heat flux have been inconsistently reported. This inconsistency makes it difficult to synthesize results from different investigations regarding the impact of unprotected timber on fire severity and self-extinction. This review paper will summarize recent large-scale CLT compartment fire tests, discuss trends in test methodology and data reporting, and identify topics in need of further research to improve understanding of the fire behavior of mass timber buildings.